Aspectos ecofisiológicos das cianobactérias em uma lagoa costeira urbana (Lagoa Juara, Serra, ES) - Alves, Fernanda Brêda (2015)
This study aimed to evaluate the cyanobacterial community structure analyzing taxonomic richness, composition, total density (individuals / mL), abundance, dominance of species beyond their biomass in Juara pond in spatial scale, vertical and temporal. Two samples were performed, one in the dry season (Sept / 2013) and another held in the rainy season (Mar / 2014) at three sampling stations located in a longitudinal gradient in the lagoon, representing regions near the mouth of streams (including those backers of matter organic resulting from domestic effluent discharge "in natura" is primarily via stream Laranjeiras), the sea andthe deployment area of the cages. Sub-surface samples were collected at depths of 50% brightness 1% light water column, always in the morning. Qualitative samples were collected with a plankton net of 20 microns and quantitative bottle with van Dorn. The cyanobacterial community structure was evaluated based on its key attributes: taxa richness, total density, abundance and dominance. The biovolume was calculated based on geometric shapes approximating the shape of the cell. Were determined: temperature (air / water), euphotic zone depth, pH, dissolved oxygen (DO), turbidity, electrical conductivity (EC) and major nutrients (silicate, nitrate, ammonia nitrogen, total nitrogen, orthophosphate, total phosphorus). We recorded 43 species of cyanobacteria, belonging to 17 genera, 8 families and 4 orders, 3 genres confirmed in literature as microcystin producers. The total density of cyanobacteria showed higher values in samples influenced by precipitation with no differences between the EA1 and EA2 station, just sampling station AE3 significant difference between the period of drought and rain, with higher density figures in the dry season. The biovolume data were higher in the rainy season and EA2 sampling station. The vertical variation of biovolume showed a significant difference only in the sampling stations EA1 and EA3, with uniform EA2 station at different depths. So the Microcystis genus had a higher contribution in terms of biovolume. The microcystin produced mainly by this genre was present in the aquatic environment, both in the dry season as in the rainy, with values within the parameters allowed by law. The values of total phosphorus, total nitrogen and nitrate showed temporal and spatial variation. The vertical variation was slight in the depths of the three sampling stations. The highest recorded concentrations of orthophosphate, total phosphorus, total nitrogen and nitrate, especially in EA2 and EA3 stations. The EA2 and EA3 stations showed limnological and biological characteristics of similarity. Both stations suffer human impact due to intensive fish farming system and through the discharge of domestic sewage "in natura" via stream Laranjeiras respectively. The Juara pond has multiple uses, and the development of subsistence activity as intensive fish farming, this practice together with the impacts associated with the injection of wastewater, showed signs of changes regarding the environmental conditions in the pond leading to the development of species-producing cyanobacteria microcystin. The presence of this toxin at high levels may impair the use of the pond, especially intensive farming of fish for consumption and leisure and recreation.